Teori Pertingkatan Norma dalam Usul Fikih - Anwar, Syamsul (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2016)
In  this  article,  the  writer  investigates  the  possibility  of  the existence of the notion of legal norm hierarchy in IslamicLaw through analysing several key concepts such as  hukm shar’i(detailed legal rule), asl kulli  (general principle),  qaidah fiqhiyyah  (legal maxim), and  kulliyyat (universals). The writer comes to the conclusion that itis possible to say the Islamic law knows the hirarchical structure of legal norms, but not  in  the  formal  sense  of  the  term,  rather  much  more  in  the substansial  one.  This  means  that  every  legal  norm  in  Islamic  Law  is based on a higher norm, but this higher norm does notfunction as a norm  which  formally  autorizes  its  making,  but  forms  a  source  from which it can be drived.